Ed Ruscha. (1st August 2013) - Colpitt, Frances
Because of its diversity and breadth, Ed Ruscha's work lends itself to seemingly infinite shuffling and parsing, classification and categorization. The number of mediums he has explored (painting, drawing, photography, printmaking, bookmaking, filmmaking, and language) is only surpassed by the variety of his subject matter, which is too numerous to list. In depictions of cars, roads, and roadside vistas, "Ed Ruscha: Road Tested" offered revealing, and at times emotional, insights into the theme of mechanized movement through the landscape